Case report: Preimplantation genetic testing for X-linked alport syndrome caused by variation in the COL4A5 gene - Liu, Nengqing; Wen, Xiaojun; Ou, Zhanhui; Fang, Xiaowu; Du, Jing; Lin, Xiufeng (Frontiers in Pediatrics, 2023)
X-Linked Alport Syndrome (XLAS) is an X-linked, dominant, hereditary nephropathy mainly caused by mutations in the COL4A5 gene, found on chromosome Xq22. In this study, we reported a pedigree with XLAS caused by a COL4A5 mutation. This family gave birth to a boy with XLAS who developed hematuria and proteinuria at the age of 1 year. We used next-generation sequencing (NGS) to identify mutations in the proband and his parents and confirmed the results using Sanger sequencing. This testing showed there was a single nucleotide missense variation, c.3659G>A (p.Gly1220Asp) (NM_033380.3), in the COL4A5 gene. To prevent the inheritance of the syndrome, we used eight embryos for trophoblast biopsy after assisted reproductive technology treatment, and whole genome amplification (WGA) was performed using multiple annealing and looping-based amplification cycles (MALBAC). Embryos were subjected to Preimplantation Genetic Testing (PGT) procedures, including Sanger sequencing, NGS-based single nucleotide polymorphism (SNP) haplotype linkage analysis, and chromosomal copy number variation (CNV) analysis. The results showed that three embryos (E1, E2, and E4) were free of CNV and genetic variation in the COL4A5 gene. Embryo E1 (4AA) was transferred after consideration of the embryo growth rate, morphology, and PGT results. Prenatal diagnosis in the second trimester showed that the fetus had a normal karyotype and did not carry the COL4A5 mutation (c.3659G>A). Ultimately, a healthy boy was born and did not carry the pathogenic COL4A5 mutation, which indicated that PGT prevented the intergenerational transmission of the causative mutation of XLAS.